La imagen de la mujer en el cuento griego moderno (Indagación sobre la cuestión del género) - García Álvarez, César (Byzantion Nea Hellás, 2015)
The aim of this article is to highlight the image of women, as shown in the modero Greek short story. To achieve this aim, the THE MODERN GREEK SHORT STOR Y "corpus" is used. This is an anthology published by the CENTRO DE ESTUDIOS GRIEGOS BIZANTINOS Y NEOHELENICOS of the UNIVERSIDAD DE CHilE in 1989. The corpus selects the most representative modero Greek short stories from the point of view of gender, compares their variations and contrasts them with the 20th century female Greek poetry. Finally, the whole study is submitted to the ancient standards "Penélope woman", "Medea woman", "Antígona woman", etc. Thus, the work shows the persistence of the classical female image in much more modero and externa! Greek texts – from the historie point of view - -than the circumstance in which the classical writers created their works.